MESH-IN: A MESHed INlet offline coupling method for 3-D extreme hydrodynamic events in DualSPHysics. (15th January 2023) - Ruffini, Gioele; Domínguez, José M.; Briganti, Riccardo; Altomare, Corrado; Stolle, Jacob; Crespo, Alejandro J.C.; Ghiassi, Bahman; Capasso, Salvatore; De Girolamo, Paolo
Abstract: Extreme hydrodynamic events, such as those driven by tsunamis, have a significant impact on coastal environments. The Smoothed Particle Hydrodynamics computational method gained popularity in modelling these phenomena. However, high resolution is needed in areas of interest, making coupling techniques popular to reduce computational costs. Herein, a new two-step offline coupling method was developed and validated in DualSPHysics. In step 1, the simulated velocity field and water depth are measured over a two-dimensional meshed surface of a generating domain. In step 2, the interpolated flow variables are used as boundary conditions in a receiving domain with equal or higher resolution. The method was validated by using two different laboratory experiments that are representative of tsunami propagation and inundation inland. The results show a reduction of computational time of up to 17.6 times, with decreasing savings for increasing resolution in the receiving domain. The validation tests showed that the developed method allows to simulate flows in the receiving domains at nearly the same accuracy of the generating domain while also decreasing computational time. When including debris transport, improvements in accuracy occur when doubling the resolution of the receiving domain with respect to the generating domain. Highlights: We present a novel coupling method for SPH called MESH-IN. MESH-IN provides boundary conditions for variables measured on a meshed surface. Validation with two different laboratory experiments is provided. MESH-IN is effective in reducing computational resources preserving accuracy.